Adat Perkawinan Masyarakat Buton di Dusun Tomi-Tomi Kecamatan Waesala, Kabupaten Seram Bagian Barat - Epa, Epa; Kubangun, Nur Aida; Acim, Acim (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2024)
This study examines the Hende Hora marriage tradition among the Buton community in Tomi-Tomi Hamlet, Waesala District, West Seram Regency. The research method used is qualitative with a descriptive approach. According to Bogdan and Taylor (in Moleong, 2005), qualitative methods produce descriptive data in the form of written or spoken words from people and observable behaviour. This research focuses on understanding social phenomena from various participants' perspectives. Data sources were obtained from traditional leaders, community leaders, religious figures, and documentation related to the Hende Hora marriage tradition. Data collection techniques included observation, interviews, and document analysis. The research findings indicate that the Hende Hora marriage is a solution for community members who wish to marry despite lacking sufficient wealth. The process includes traditional rituals such as kabubusikakeno (foot washing) and kapusuko (draping with cloth). Although performed, this marriage is still respected and holds value equal to other traditional marriages in Southeast Sulawesi. The religious and cultural values embedded in this tradition highlight the importance of customs in shaping personality and social relationships within the Buton community. This study confirms that the Hende Hora tradition is still maintained and recognized in Tomi-Tomi Hamlet.